Implementing Skilled Midwifery Services in Dhaka City Urban Area: Experience from Community Based Safe Motherhood Project, Bangladesh - Tasnim, S; Rahman, A; Rahman, F; Kabir, N; Islam, F; Chowdhury, S; Shahabuddin, AKM (Journal of Bangladesh College of Physicians and Surgeons, 2011)
In Bangladesh majority of deliveries are attended by unskilled traditional birth attendants and maternal mortality is still quite high. Global evidence suggests that most critical intervention for reduction of maternal mortality is to ensure skilled attendance at birth. The objective of this study was to explore the effect of strengthening obstetric care services through implementation of skilled Midwives at selected urban centres in terms of utilization of antenatal and delivery care in the community. A quasi experimental community trial was conducted during January 2000 to June 2003. Ten health centers were selected from the maternity care centers of urban primary health care project in Dhaka city, matched into comparable pair and assigned randomly as intervention and control centers. The intervention consisted of deployment of 10 skilled midwives in pair to provide obstetric care services in five intervention centre and the community. Essential drugs and logistics were supplied to both intervention and control centers for optimizing the function. A total of 6077 mothers having less than one year child were interviewed. There was significant improvement from baseline in the utilization of antenatal care services (6.1 vs. 2.1%, p<0.001), availing antenatal visits 5 times or more (13.4% vs. 8.1%, p<0.001), consultation with skilled health care providers for pregnancy complication (9.3% vs. 5.7 %, p<0.001), institutional delivery (7.3% vs. 4.1%, p<0.001) and delivery by skilled birth attendant (9.4% vs. 5.8%, p<0.001) between intervention and control area respectively. The intervention of deployment of skilled midwives improved utilization of ANC, increased institutional delivery and delivery by skilled birth attendants. The program can be scaled up to see its impact on maternal health. Key words: skilled midwife; emergency obstetric care; urban health care; antenatal care DOI: 10.3329/jbsp.v29i1.7165 J Bangladesh Coll Phys Surg 2011; 29:10-15